Assessment of photovoltaic thermal efficiency using phase change material and water-channel collector with T-fin design - Mohd Rosli, Mohd Afzanizam; Low, Zi Qing; Salimen, Nurfarhana; Abdul Rashid, Azrin Hani; Herawan, Safarudin Gazali (Semarak Ilmu Publishing, 2025)
Photovoltaic thermal systems, also known as hybrid solar panels, combine photovoltaic and solar thermal components to generate both electrical and heat energy from the sun. Despite solar energy has significant potential, conventional photovoltaic systems suffer from low efficiencies due to the wasted heat energy and high working temperature. This research aims to develop and examine the efficiency of a photovoltaic thermal system integrated with commercial phase change material (PCM) using copper T-fin absorber to increase solar energy conversion efficiency. The research involved fabricating aluminium packets for commercial PCM, filling fabricated packets into a developed photovoltaic thermal system with T-fin absorber, and conducting final experiments under three different water flow rates for each of three different irradiance levels under solar simulator with 30 minutes run for each test. The final experiment assessed temperature difference, electrical efficiency, thermal efficiency, and overall efficiency. At 800 W/m2 and 90 l/h, the highest temperature drop was 11.20°C. The highest electrical efficiency of 8.0% was achieved at 800 W/m2 and 90 l/h. The highest thermal efficiency was 72.5% at 400 W/m2 and 90 l/h. The highest overall efficiency of 79.8% at 400 W/m2 and 90 l/h for the T-fin absorber. These results concluded the enhanced heat transfer capability and contribution to higher overall system efficiency after integrated commercial PCM and T-fin absorber.